Parenting moderates the etiology of callous‐unemotional traits in middle childhood. (18th November 2021) - Tomlinson, Rachel C.; Hyde, Luke W.; Dotterer, Hailey L.; Klump, Kelly L.; Burt, S. Alexandra
Abstract : Background: Callous‐unemotional (CU) traits are associated with chronic and escalating trajectories of antisocial behavior. Extant etiologic studies suggest that heritability estimates for CU traits vary substantially, while also pointing to an environmental association between parenting and CU traits. Methods: We used twin modeling to estimate additive genetic (A), shared environmental (C), and nonshared environmental (E) influences on CU traits, measured with the Inventory of Callous‐Unemotional Traits (ICU) and its subscales. Our sample included 600 twin pairs (age 6–11, 230 monozygotic) from neighborhoods with above‐average levels of family poverty, a risk factor for antisocial behavior. We examined the extent to which correlations between parenting, measured via parent and child report on the Parental Environment Questionnaire, and CU traits reflected genetic versus environmental factors. Then, we tested whether parenting moderated the heritability of CU traits. Results: In the context of lower‐income neighborhoods, CU traits were moderately to highly heritable ( A  = 54%) with similar moderate‐to‐high nonshared environmental influences ( E  = 46%). Bivariate models revealed that associations between CU traits and warm parenting were genetic (rA = .22) and environmental (rE = .19) in origin, whereas associations between CU traits and harsh parenting were largely genetic in origin (rA = .70). The heritability of CU traits decreased with increasing parental warmth and decreasing harshness. Conclusions: Callous‐unemotional traits are both genetic and environmental in origin during middle childhood, but genetic influences are moderated by parenting quality. Parenting may be an important target for interventions, particularly among youth with greater genetic risk.